DNA Content Estimation in the Genus Salvia - Rebekah C.I. Maynard; John M. Ruter (Journal of the American Society for Horticultural Science, 2022)
Salvia is a genetically diverse genus in the Lamiaceae family, with hundreds of species distributed globally. With base chromosome numbers ranging from 6 to 19 and ploidy levels ranging from diploid to octoploid, the genus has been proposed to be subdivided based on molecular data rather than morphology. However, little is known about total DNA content across the genus. The DNA content of 141 Salvia genotypes were analyzed using flow cytometry. Samples of Salvia were stained with propidium iodide and compared with the internal standards Pisum sativum ‘Ctirad’ and Solanum lycopersicum ‘Stupické’ to generate estimations of DNA content. Holoploid 2C genome sizes of the analyzed Salvia ranged from 0.63 pg to 6.12 pg. DNA content showed a wide distribution across chromosome number, ploidy, and clade. The wide distribution of DNA content across the genus further indicates the diversity of Salvia and may be useful for future breeding efforts.